2011
DOI: 10.1007/s10482-011-9554-5
|View full text |Cite
|
Sign up to set email alerts
|

A method to type the potential angucycline producers in actinomycetes isolated from marine sponges

Abstract: Angucyclines are aromatic polyketides with antimicrobial, antitumor, antiviral and enzyme inhibition activities. In this study, a new pair of degenerate primers targeting the cyclase genes that are involved in the aromatization of the first and/or second ring of angucycline, were designed and evaluated in a PCR protocol targeting the jadomycin cyclase gene of Streptomyces venezuelae ISP5230. The identity of the target amplicon was confirmed by sequencing. After validation, the primers were used to screen 49 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The identities ranged from 96.5% to 100% identity over a region of 1340 bp and the bacteria belonged to the following phyla: Actinobacteria , Firmicutes and Proteobacteria ( Alphaproteobacteria and Gammaproteobacteria ). Unexpectedly the Firmicutes and Gammaproteobacteria were the phyla which showed the most antibacterial activities as opposed to the Actinobacteria , well-known for their antibiotic activities [9,64,65]. …”
Section: Resultsmentioning
confidence: 99%
“…The identities ranged from 96.5% to 100% identity over a region of 1340 bp and the bacteria belonged to the following phyla: Actinobacteria , Firmicutes and Proteobacteria ( Alphaproteobacteria and Gammaproteobacteria ). Unexpectedly the Firmicutes and Gammaproteobacteria were the phyla which showed the most antibacterial activities as opposed to the Actinobacteria , well-known for their antibiotic activities [9,64,65]. …”
Section: Resultsmentioning
confidence: 99%
“…Streptomyces is a well-known polyketide producer, so it is not surprising that KS α gene was identified in all the 4 Streptomyces strains. Prior to this study, it was found that most of the Micromonospora strains are not potential producers of type II polyketides [26], [33]. The known secondary metabolites produced by Micromonospora are mainly aminoglycosides, macrolides and enediynes, few aromatic polyketides are known to be produced by Micromonospora except anthracyclines [46].…”
Section: Discussionmentioning
confidence: 93%
“…Cycling conditions were as follows: initial denaturation at 95°C for 5 min, 30 cycles of 95°C for 35 s, 55°C for 40 s, and 72°C for 1 min, and a final extension of 10 min at 72°C. The degenerate primers AuF3 (5′-GAACTGGCCSCGSRTBTT-3′) and AuR4 (5′-CCNGTGTGSARSKTCATSA-3′) were applied in the amplification of angucycline cyclase gene [33]. 20 µl PCR mixtures included 10 µl Taq Premix, 1 µl AuF3 (40 µM), 1 µl AuR4 (40 µM) and 5% DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…Ouyang et al [75] designed the PCR primers targeting jadomycin cyclase, which catalyzes the aromatization of the first and/or second ring of angucycline. Based on this degenerate primer, angucycline-producing actinobacteria were identified from three different marine sponge species.…”
Section: Polyketidesmentioning
confidence: 99%
“…Two known compounds A-3302-A (73) and A-3302-B (74), N-acetyl-Lphenylalanyl-L-leucinamide (75) and new compounds nobilamides A-H (76-83) were isolated from mollusc-associated Streptomyces sp. CN48 based upon their suppression of capsaicin-induced calcium uptake in a mouse dorsal root ganglion primary cell culture assay.…”
Section: Peptidesmentioning
confidence: 99%